Sistem Penunjang Keputusan Seleksi Penerimaan Dana Bantuan Operasional Sekolah (BOS) Bagi Siswa/Siswi Yang Kurang Mampu Dengan Metode Simple Multi Attribute Rating Technique (SMART) (Studi Kasus : SDN Karang Tengah 7) - Muhammad Afif Fadilah; Ari Syaripudin (CV. Multi Kreasi Media, 2022)
The School Operational Assistance Fund is a government program that is basically for the provision of non-personnel operational cost funds for basic education units as implementers of the 9-year compulsory education program The specific purpose of BOS funding at the elementary school (SD) education level is to reduce and waive the costs of all students in both public and private schools. At SDN Karang Tengah 7, for example, to determine the recipients of school operational assistance funds (BOS) is still determined manually so that the target is not right for underprivileged students. Therefore, the purpose of this study is to make it easier for the school to determine prospective students who receive school operational assistance funds (BOS) to be more targeted. To find out how to determine the students who receive school operational assistance funds (BOS), the author uses the Simple Multi Attribute Rating Technique (SMART) method. Decision-making will be easier to determine who is entitled to receive school operational assistance funds (BOS) so that it is right on target. From the results of this study, a system was produced that can be used to determine who is entitled to receive the aid funds to be right on target at SDN Karang Tengah 7.